Effects of morphine on human pancreatic secretion: studies on pure pancreatic juice. Issue 9 (September 1982) - Gullo, L; Priori, P; Costa, P L; Garcea, D; Baldoni, F; Mattioli, G; Labo, G
Abstract : Data concerning the effects of morphine on human pancreatic secretion are fragmentary and inconclusive. In the present study, we evaluated the effects of morphine on pure pancreatic secretion in nine subjects with external transduodenal drainage of the main pancreatic duct performed after biliary tract surgery. Intravenous infusion of a small dose of morphine, 40 microgram/kg/h, during pancreatic stimulation with secretin and cholecystokinin, caused a significant increase in volume, bicarbonate, and calcium secretion, and a significant decrease in protein secretion. The stimulatory effect on water and electrolyte secretion was rapid and much more pronounced, reaching about 45-50% of the control levels, whereas the inhibition of protein output was slightly delayed and of lesser magnitude, reaching about 20-25% of the control values. Both effects were long-lasting. The addition of naloxone, potent opiate antagonist, prevented in part the effects of morphine on pancreatic secretion, suggesting that specific opiate receptors might be involved in these effects.